Etnofisiologi Pertuq sebagai Pengobatan Tradisional Upaya untuk Mewujudkan Good Health and Well-being di Lombok Timur - Suriani, Yunisa; Ukhro, Ahmad Izzatul; Junaidi, Junaidi; Zohriani, Zohriani; Kusuma, Anindita SHM (Jurnal Ilmiah Profesi Pendidikan, 2025)
This study examines the ethnophysiological basis of the Pertuq practice as a form of traditional healing still actively practiced by the people of Sakra District, East Java. Pertuq is performed to treat a condition known as ketemuq, a disorder believed to originate from the influence of ancestral spirits. The study used a qualitative approach with an ethnophysiological design through direct observation, in-depth interviews with Pertuq practitioners, community leaders, and individuals who have undergone the ritual, and instrument review. Thematic analysis shows that the Pertuq practice proceeds through structured stages, including symptom identification, determination of spiritual disorders, pulling the hair at the crown of the head nine times, reciting the intention, saying bismillah (bismillah), Surah Al-Fatihah, reciting the name of the penemuq, and a closing prayer. This practice reflects the Sakra community's understanding of the body as a physical, emotional, and spiritual unity. Physiologically, the sensations that arise during the ritual are related to the activation of the autonomic nervous system in response to stress. Psychologically, Pertuq provides calm, reduces anxiety, and strengthens the patient's faith through culturally based healing mechanisms. The research confirms that Pertuq plays a role as a traditional health strategy that helps maintain physical and mental balance and complements modern medical treatment in supporting good health and well-being.